O ensino da filosofia no Brasil : um mapa das condições atuais - Fávero, Altair Alberto (2004)
This article results from a research developed in Brazil in the year 2003, in accordance with the request of UNESCO, aiming at outlining the conditions of philosophy teaching in this country, in their variegated levels, with special emphasis in high school. Therefore, the article does not constitute an analytical effort but offers a description in the most detailed way of the diverse conditions of the teaching of philosophy in different Brazilian regions in this moment